GENDER PARTICIPATION IN CASSAVA PROCESSING IN IMO STATE NIGERIA (FULafia Journal of Science and Technology, 2019)
Gender participation in cassava processing in Imo State, Nigeria was investigated. Purposive and multi-stage random sampling techniques were used in the selection of a total of 240 farmers consisting of 120 male and 120 female cassava farmers. Instrument for data collection was a structured and pre-tested questionnaire and descriptive and inferential statistics were used to analyze the data generated. Majority of respondents (93.0% of males and 90.0% of females) were within the age range of 20 to 59; had formal education (97.0% of males and 95.5% of females); were married (74.0% males and 77.0% females); and had 4-9 persons per household. More males (27.0%) than females (6.0%) did not process their roots suggesting that they sold off their roots for cash while women processed probably to feed their family and then sell any surpluses. The mean distance from houses to processing centres of 2.0km and 1.69km respectively for male and female respondents suggest that males travel longer distances to process their cassava roots while females patronize those centres that were nearer.